2016
DOI: 10.1085/jgp.201611601
|View full text |Cite
|
Sign up to set email alerts
|

Polymodal activation of the TREK-2 K2P channel produces structurally distinct open states

Abstract: TREK channels, which are gated open by a wide range of stimuli, exist in at least two conformations known as “up” and “down.” McClenaghan et al. show that the channel can be open in both of these conformations and that gating is primarily achieved by the channel’s selectivity filter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 32 publications
12
95
0
Order By: Relevance
“…This is therefore consistent with the lower pressures required for functional activation of TREK-2. Overall this demonstrates that increasing lateral tension quickly expands the bilayer, and that these changes produce a down to up conformational change consistent with our proposed model for mechanogating of K2P channels (Figure 1B) (Dong et al., 2015, McClenaghan et al., 2016). In further agreement with this model, the up state structure (4BW5) exhibits a highly stable conformation when subjected to the P-50 stretch protocol (Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is therefore consistent with the lower pressures required for functional activation of TREK-2. Overall this demonstrates that increasing lateral tension quickly expands the bilayer, and that these changes produce a down to up conformational change consistent with our proposed model for mechanogating of K2P channels (Figure 1B) (Dong et al., 2015, McClenaghan et al., 2016). In further agreement with this model, the up state structure (4BW5) exhibits a highly stable conformation when subjected to the P-50 stretch protocol (Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…The NFx-bound crystal structure of TREK-2 (4XDL) was used as a guide to place the drug in its binding site and the structure then simulated with and without membrane stretch. As predicted from our previous functional studies (Dong et al., 2015, McClenaghan et al., 2016), the presence of NFx in its binding site in the upper part of the fenestration (Figure 4E) interfered with closure of the interface between M4 and adjacent M2, thus slowing movement toward the up state (Figure 4F). This is also consistent with our previous functional studies which show that NFx markedly slows the kinetics of stretch activation (Dong et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, while depolarization-induced desensitization may explain observations in roughly a third of desensitized neurons, for the majority we believe a more likely explanation is the possibility that peripheral terminals instead became hyperpolarized through direct and/or indirect actions of one or more ingredients in the inflammatory soup, presumably through increased potassium conductance. For example, TREK2 channels expressed in many C fibers (Acosta et al, 2014), are activated by protons (McClenaghan et al, 2016; Sandoz et al, 2009). Further, it is well known that other mediators in the soup (e.g., bradykinin, prostaglandin E2, histamine, and serotonin) can stimulate production of nitric oxide in a variety of cell types and may thus indirectly activate ATP-sensitive potassium channels in sensory neurons (Chi et al, 2007; Du et al, 2011; Kawano et al, 2009; Zoga et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although both the up and down conformations of TREK-2 can be conductive, our previous studies have shown that stretch activation preferentially stabilizes the up conformation, and that this has a positive allosteric effect on the filter gating mechanism (31,33). The precise relationship between the different conformational states of any ion channel and their behavior at the single-channel level is complex and not fully understood, however.…”
Section: Stretch Activation Preferentially Destabilizes a Closed Statmentioning
confidence: 96%
“…We have recently shown how increased (symmetrical) lateral tension within the lipid bilayer induces a structural change in TREK-2 from the "down" state of the channel to the more expanded "up" state conformation (31,33,34). However, unlike the nonselective prokaryotic MS channels, in which stretchinduced expansion dilates the central pore, K2P channels remain highly K + -selective (35).…”
Section: Significancementioning
confidence: 99%